1975
DOI: 10.1002/star.19750270702
|View full text |Cite
|
Sign up to set email alerts
|

Elektronenmikroskopischer Beitrag zur Kenntnis der Feinstruktur der Weizenstärke

Abstract: Electron Microscope Contribution to the Study of Fine Structure of Wheat Starch. Electron microscope investigations of the fine structure of wheat starch granules were carried out using a combined fixation and staining technique. It was found that amylose is particularly concentrated in the nucleus. Uranophilic layers seem to indicate the presence of protein in the outermost surface regions of the starch granules, The radial orientation of the helicoidal unit chains of amylopectin could be confirmed. In both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In the PATAg method, the dialdehydes react with thiosemicarbazide instead of Schiff reagent forming thiosemicarbazones, which effectively reduce silver proteinate and release metallic silver at the sites of glycol linkages (Hayat 1989). The PATAg method has been successfully used for electron microscopy investigation of starch granule ultrastructure (Kassenbeck 1975(Kassenbeck , 1978Gallant and Bouchet 1986;Planchot et al 1995;Gallant et al 1997). The PATAg reaction produces a very fine reaction product and is almost free of nonspecific precipitates (Hayat 1989), which leads to a good contrast in thin sections of starch granules.…”
Section: Periodic Acid-thiosemicarbazide-silver Protenate and Ammoniamentioning
confidence: 99%
See 1 more Smart Citation
“…In the PATAg method, the dialdehydes react with thiosemicarbazide instead of Schiff reagent forming thiosemicarbazones, which effectively reduce silver proteinate and release metallic silver at the sites of glycol linkages (Hayat 1989). The PATAg method has been successfully used for electron microscopy investigation of starch granule ultrastructure (Kassenbeck 1975(Kassenbeck , 1978Gallant and Bouchet 1986;Planchot et al 1995;Gallant et al 1997). The PATAg reaction produces a very fine reaction product and is almost free of nonspecific precipitates (Hayat 1989), which leads to a good contrast in thin sections of starch granules.…”
Section: Periodic Acid-thiosemicarbazide-silver Protenate and Ammoniamentioning
confidence: 99%
“…A number of techniques, such as differential scanning calorimetry (DSC), X-ray diffractometry, nuclear magnetic resonance (NMR), chromatography, mass spectrometry, and electron microscopy combined with cytochemical techniques have been used to study the structure of starches. Of these, only the latter enables a direct visualization of starch granule morphology and ultrastructure with or without the need for prior physical, chemical, and enzymatic treatments (Kassenbeck 1975(Kassenbeck , 1978Nikuni 1978;Yamaguchi et al 1979;Gallant and Bouchet 1986;Oostergetel and Bruggen 1989;Fannon et al 1993;Planchot et al 1995;Helbert and Chanzy 1996;Garcia et al 1997;Atkin et al 1998a,b). Our previous studies (Li et al 2001a,b) indicated that the composition, granule structure, amylopectin chain length profile, and physicochemical properties of hull-less barley (HB) starches differ among genotypes.…”
mentioning
confidence: 99%
“…The results, if valid mathematically, are compatible with an outer ''shell" containing amylose-LPC inclusion complexes together with amylopectin. This view is not necessarily incompatible with the theory of Kassenheck [36] and others that an amylose-rich core exists at the centre of the A-type granules.…”
Section: --Imentioning
confidence: 57%
“…There is no evidence that the absolute amount of protein in the starch granules is correlated with degradability. However, starch granules may contain minor amounts of proteins and lipids, residues of the amyloplast [13,14,151. The distribution of the proteins and lipids on the surface of the starch granules may be more important than the absolute amount of protein [4].…”
Section: Discussionmentioning
confidence: 99%